Bilateral angiosarcoma of breast in a young lady - Sanjoy Roy; Devleena; Tapas Maji; Prabir Choudhuri; Jaydip Biswas; Debarshi Lahiri (Indian Journal of Medical and Paediatric Oncology)
We report a young lady with bilateral angiosarcoma of breast because of its rarity. A 29 year old unmarried female presented with bilateral breast lump. She underwent bilateral mastectomy with axillary dissection histopathology of which showed low grade angiosarcoma of left breast and high grade angiosarcoma of right breast. CT Thorax revealed right hilar and right mediastenal lymph nodes. She was treated with radiotherapy and chemotherapy postoperatively.